Developing a fuzzy-based model to assess and allocate risks in Syrian construction projects - Reem Ghanem Kattoub; Jamal Omran (Tishreen University, 2023)
Construction industry has always been a place of growing interest. It is mostly known, however, for its poor reputation for managing risks that inevitably come across a great number of the activities it involves. Those risks are simply described as a disruption for what is a rather normal task. Some of those risks can be impactful in a way that cannot be foreseen and would be catastrophic for the client and for the contractor. Assessing and allocating risks in a construction project is then a key component of an integrated, efficient, and successful risk management of every construction project. It is, however, shrouded with ambiguity, uncertainty, human judgment, and natural expressions. This makes fuzzy-based approaches more suitable to make a final assessment. This paper aims to develop a fuzzy-based model to predict major risks liability and magnitude based on a series of questionnaire with experienced engineers in Lattakia, Syria. This prototype model is developed using Matlab and fuzzy-set theory to make more reliable decisions and to avoid costly overruns especially in the early phases of the project where few or no information is available.